Validating the rigour of adaptive methods of economic evaluation - Nidhi Gupta; Shankar Prinja; Abha Mehndiratta; Akashdeep Singh Chauhan; Deepshikha Sharma; Basant Garg; Amneet P Kumar (BMJ Global Health)
Background There has been a lot of debate on how to ‘generalise’ or ‘translate’ findings of economic evaluation (EE) or health technology assessment (HTA) to other country contexts. Researchers have used various adaptive HTA (aHTA) methods like model-adaptation, price-benchmarking, scorecard-approach, etc., for transferring evidence from one country to other. This study was undertaken to assess the degree of accuracy in results generated from aHTA approaches specifically for EE.Methods By applying selected aHTA approaches, we adapted findings of globally published EE to Indian context. The first-step required identifying two interventions for which Indian EE (referred to as the ‘Indian reference study’) has been conducted. The next-step involved identification of globally published EE. The third-step required undertaking quality and transferability check. In the fourth step, outcomes of EE meeting transferability standards, were adapted using selected aHTA approaches. Lastly, adapted results were compared with findings of the Indian reference study.Results The adapted cost estimates varied considerably, while adapted quality-adjusted life-years did not differ much, when matched with the Indian reference study. For intervention I (trastuzumab), adapted absolute costs were 11 and 6 times higher than the costs reported in the Indian reference study for control and intervention arms, respectively. Likewise, adapted incremental cost and incremental cost-effectiveness ratio (ICER) were around 3.5–8 times higher than the values reported in the Indian reference study. For intervention II (intensity-modulated radiation therapy), adapted absolute cost was 35% and 12% lower for the comparator and intervention arms, respectively, than the values reported in the Indian reference study. The mean incremental cost and ICER were 2.5 times and 1.5 times higher, respectively, than the Indian reference study values.Conclusion We conclude that findings from aHTA methods should be interpreted with caution. There is a need to develop more robust aHTA approaches for cost adjustment. aHTA may be used for ‘topic prioritisation’ within the overall HTA process, whereby interventions which are highly cost-ineffective, can be directly ruled out, thus saving time and resources for conducting full HTA for interventions that are not well studied or where evidence is inconclusive.